An update on the spider genus Caponina Simon (Araneae: Caponiidae) with descriptions of three new six-eyed species from Colombia - Sánchez-Ruiz, Alexander; Martínez, Leonel; Bonaldo, Alexandre B. (European Journal of Taxonomy, 2022)
Three new six-eyed species of the spider genus Caponina Simon, 1891 are described, photographed, diagnosed and illustrated: C. alejandroi sp. nov. (male and female) from the Boyacá Department, C. bochalema sp. nov. (male) from the Santander Department and C. huila sp. nov. (male) from the Huila Department. Also, a emended diagnosis for the genus, a distribution map and an identification key for all species of Caponina are provided.